The Effectiveness of Using the Al-Muhawarah Book to Develop Arabic Speaking Skills at Riyad al-Salihin Islamic Junior High School - Muhammad Wasi Bikunnun; Shobirin Shobirin (Al-Muyassar: Journal of Arabic Education, 2025)
This study aimed to evaluate the effectiveness of the Muhawarah textbook in enhancing Arabic speaking skills among students at MTs Riyadlus Sholihin. The research adopted a classroom action research design using a cyclical model comprising planning, implementation, observation, and reflection stages, carried out over two cycles. In Cycle 1, students engaged in introductory speaking activities using the textbook, with data gathered through observations, speaking assessments, and questionnaires. In Cycle 2, the program expanded to include varied exercises and group discussions to further develop speaking abilities. The results showed notable improvement in students’ Arabic speaking skills, particularly in fluency, pronunciation, and grammatical accuracy. Student motivation and confidence in speaking also increased, as evidenced by more active participation during class discussions and speaking tasks. Quantitatively, student understanding improved from 60% in the pre-cycle to 70% in Cycle 1, and further to 90% in Cycle 2. By the end of Cycle 2, 30 students demonstrated excellent mastery of Arabic speaking, following Nahwu and Sorrof rules accurately. The study concludes that the Muhawarah textbook is highly effective in improving students’ speaking skills and recommends its integration into the Arabic curriculum. Additionally, it emphasizes the need for continuous teacher training to optimize textbook use in enhancing learning outcomes. Keywords: Effectiveness, Muhawarah Textbook Learning, Arabic Languageمستخلص البحثهد? هذا البحث إلى تقييم ?اعلية كتاب المحاورة ?ي تنمية مهارات التحدث باللغة العربية لدى طلاب مدرسة متوسطة رياض الصالحين الإسلامية. وقد اعتمد البحث على منهج البحث الإجرائي الص?ي باستخدام نموذج دائري يتأل? من أربع مراحل: التخطيط، والتن?يذ، والملاحظة، والتقويم، وذلك عبر دورتين متتاليتين. ?ي الدورة الأولى، شارك الطلاب ?ي أنشطة تمهيدية للتحدث باستخدام الكتاب، وتم جمع البيانات من خلال الملاحظات، وتقييمات التحدث ال?ردية، والاستبيانات. و?ي الدورة الثانية، تم توسيع البرنامج ليشمل تدريبات متنوعة ومناقشات جماعية لتعزيز مهارات التحدث بشكل أعمق. أظهرت نتائج الدراسة تحسناً ملحوظاً ?ي مهارات التحدث لدى الطلاب، ولا سيما ?ي الطلاقة والنطق والدقة النحوية. كما ارت?عت دا?عية الطلاب وثقتهم ?ي التحدث، وهو ما انعكس ?ي مشاركتهم النشطة ?ي المناقشات الص?ية والأنشطة الش?وية. من الناحية الكمية، تحسّن مستوى ?هم الطلاب من 60٪ ?ي المرحلة التمهيدية إلى 70٪ ?ي الدورة الأولى، ثم إلى 90٪ ?ي الدورة الثانية. وبنهاية الدورة الثانية، أظهر ثلاثون طالباً إتقاناً ممتازاً لمهارة التحدث باللغة العربية، و?قاً لقواعد النحو والصر?. وتخلص الدراسة إلى أن كتاب المحاورة ?عّال بدرجة عالية ?ي تحسين مهارات التحدث لدى الطلاب، وتوصي بإدماجه ضمن المنهج الدراسي لمادة اللغة العربية. كما تؤكد على ضرورة تو?ير تدريب مستمر للمعلمين لتعظيم الاست?ادة من هذا الكتاب ?ي تحسين مخرجات التعلم. الكلمات الم?تاحية:  ?عالية، كتاب المحاورة ، تعليم اللغة العربية.